PELATIHAN MOBILE BANKING KEPADA MASYARAKAT DESA BOJONGMANGU UNTUK MENGHADAPI ERA SOCIETY 5.0 - Apriliani, Niken Cahya; Putra, Purnama; Fahlevi, Rizal; Khoiriyah, Ummi (LPPM Universitas Islam 45, 2024)
Mobile banking training for the Bojongmangu Village community aims to prepare them for the era of society 5.0. The training focused on strengthening the understanding of digital financial technology, efficient financial management, and utilization of digital banking services to expand access to Islamic finance. The service method applies training and education in understanding material related to Islamic banking with a series of practical and interactive sessions. Participants will be equipped with the skills and knowledge needed to optimize the benefits of digital financial technology in their daily lives and also an introduction to Islamic bank products. The results of community service activities in mobole banking training are to increase financial inclusion at the village level and help the Bojongmangu community to become more financially independent in the rapidly growing digital era and attract public interest in opening accounts at Islamic banks.